Recurrent embodied energy and its relationship with service life and life cycle energy: A review paper. Issue 3 (2014) - ,; ,; ,; ,
Abstract : Purpose – The recurrent embodied energy (REE) is the energy consumed in the maintenance, replacement and retrofit processes of a facility. The purpose of this paper was to analyze the relationship of REE with the service life and life cycle embodied energy. The amount of variation in the reported REE values is also determined and discussed.Design/methodology/approach – A qualitative approach that is known as the literature based discovery (LBD) was adopted. Existing literature was surveyed to gather case studies and to analyze the reported values of REE.Findings – The reported values of REE showed considerable variation across referred studies. It was also found that the reported REE values demonstrated a moderate positive correlation with the service life but a very strong positive correlation with the life cycle embodied energy of both the residential and commercial facilities.Research limitations/implications – This review paper pointed out the importance of the maintenance and replacement processes in reducing the life cycle energy use in a facility. Future research could focus on performing case studies to evaluate this relationship.Practical implications – The findings highlight the significance of REE in reducing the life cycle energy impacts of a facility. As facility managers routinely deal with maintenance and replacement processes, they hold an important responsibility of reducing the life cycle energy.Originality/value – The findings of the paper would motivate the facilities management professionals to prefer long service life materials and components during the postconstruction phases of a built facility.